2017
DOI: 10.5505/agri.2017.24392
|View full text |Cite
|
Sign up to set email alerts
|

Quadratus Lumborum Block for both cholecystectomy and right sided nephrectomy

Abstract: The quadratus lumborum block (QLB) is a unilateral facial plane block, which extends from T4 to L1 at the paravertebral space. Injecting local anesthetic between the facial plane of the quadratus lumborum muscle and the psoas major muscle provides the block of the referred dermatomes. However, the number of published studies for QLB used in various surgical procedures is limited. In this case report, we share the results of a 46-years-old ASA I female patient, who underwent open surgery for cholecystectomy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The ultrasound-guided QLB technique was first described by Blanco [11,12], and the benefits of QLB for postoperative pain relief and an opioid-sparing effect have been reported by several randomized controlled trials and case reports [2,5,6,[8][9][10][19][20][21][22][23][24][25][26][27][28][29][30]. All approaches have proven the synergistic efficacy for multimodal analgesia, especially for QLB2 or QLB3 after laparoscopic surgery, cesarean section, and total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasound-guided QLB technique was first described by Blanco [11,12], and the benefits of QLB for postoperative pain relief and an opioid-sparing effect have been reported by several randomized controlled trials and case reports [2,5,6,[8][9][10][19][20][21][22][23][24][25][26][27][28][29][30]. All approaches have proven the synergistic efficacy for multimodal analgesia, especially for QLB2 or QLB3 after laparoscopic surgery, cesarean section, and total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The quadratus lumborum block (QLB) was first described by Blanco in 2007, and later was subdivided into three basic approaches known as QLB1, 2, and 3, as well as a modified approach called intramuscular QLB, each based on needle tip position and the spread of local anesthetic (LA) [1]. Recently, numerous case reports and randomized trials have shown that QLB may be effective in relieving postoperative pain and providing an opioidsparing effect after various surgical procedures [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…33 The case reports and series reviewed in this paper uniformly reported excellent analgesic control following quadratus lumborum block for a Local and Regional Anesthesia 2021:14 variety of different nephrectomy types. [34][35][36][37][38][39][40][41] These case studies can be seen in more detail in Table 4. Like with opioid reduction, the randomized controlled trials along with observational studies show the quadratus lumborum blocks are successful in controlling postoperative pain in patients receiving laparoscopic nephrectomy.…”
Section: Pain Control Nephrectomy With Qlbmentioning
confidence: 99%
“…Ultrasound-guided QLB technique was first described by Blanco [11,12], and the benefits of QLB for postoperative pain relief and opioids-sparing effect have been reported by several randomized controlled trials and case reports [2,5,6,[8][9][10][19][20][21][22][23][24][25][26][27][28][29][30]. All approaches have been proved the synergistic efficacy for multimode analgesia, especially for QLB2 or QLB3 after laparoscopic surgery, cesarean section and total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The quadratus lumborum block (QLB) was first described by Blanco in 2007, which later can be subdivided into three basic approaches, known as QLB1, 2, 3 and a modified approach, called intramuscular QLB, based on needle tip position and the spread of local anesthetic (LA) [1]. Recently, an increasing case reports and randomized trials have show that QLB may be effective in postoperative pain relief and opioids-sparing effect after various surgery operations [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%